Exploration of Polymetallic Nodules - Madureira, Pedro (2022)
Polymetallic nodules are known to occur in the vast abyssal plains at water depths greater than 4000 m. They have been particularly well identified in the Pacific Ocean, where they were targeted for commercial extraction during several pilot-mining initiatives that took place in the 1970s. Most current exploration activities searching for these deposits are concentrated around the international seafloor, named “the Area” by the United Nations Convention on the Law of the Sea (UNCLOS), where the activities are carried out under the jurisdiction of the International Seabed Authority (ISA). Since 2001, the ISA has granted 19 contracts for exploration of polymetallic nodules, 18 in the Pacific and 1 in the Indian basin. According to the ISA regulations, the term “Exploration” means the search for extractable concentrations of polymetallic nodules in the Area. The contracts provide companies with exclusive rights to carry out studies on the environmental, technical, economic, commercial, and other appropriate factors that must be taken into account in the future exploitation of these nodules. Some of the challenges of the exploration work are addressed in this Special Issue, which is focused on the geological assessment of this particular marine mineral resource.